Konsep Islam Wasathiyah Perspektif KH. Hasyim Muzadi (Telaah Surah al-Baqarah Ayat 143) - Muhammad Al Fikri; Qathrun Nada (Pusat Kajian Moderasi Beragama dan Ideologi Pancasila UIN Sulthan Thaha Saifuddin Jambi, 2024)
The number of extreme cases that occur in Indonesia is a focus for the author. It is a great achievement when Indonesia is able to survive in the midst of various differences it has, both race, religion, customs, foreign cultures and so on. However, it cannot be denied that sometimes conflicts in Indonesian society often occur both horizontally and vertically. This study, wants to try to explore the elements contained in the Qur'an, related to wasathiya Islam in the perspective of an Indonesian figure KH. Hasyim Muzadi who has a very strong influence in the establishment of interfaith relations and is one of the figures who often acts as a mediator in all matters relating to religion and the state. This research can be a driving force to form Muslims who are in the middle, not extreme right or extreme left and willing to accept various differences as long as they are in the level of khilafiyah. This research uses qualitative library research methods and content analysis. The formulation of the problems in this study are 1). what is the meaning of wasathiyah Islam. 2). How95Konsep Islam Wasathiyah Perspektif KH.Hasyim Muzadi…Muhamnad Al Fikri & Qathrunnadadoes KH. Hasyim Muzadi think about religious moderation (wasathiyah Islam). 3). How is the interpretation of Al-Qur'an surah al-Baqarah verse 143 about wasathiyah Islam?Primary sources in this study are books related to the thoughts of KH. Hasyim Muzadi including true Islam, Islam from the heart and various literature on wasathiyah Islam. The results of this research are (1) The results of the study prove that in the Qur'an wasathiyah Islam is explained in Q.s.al-Baqarah: 143. Interpreters explain that wasathiyah Islam is interpreted as a middle society, the chosen people, and the best people. The middle attitude is realized through several things, such as the middle in addressing the world and the hereafter, humans who reflect justice, and are able to be role models for others. (2) According to KH. Hasyim Muzadi, Allah has made Muslims the chosen people among other people. People who are able to apply 3 forms of justice, namely justice of equity, justice of equality and justice of balance (3) Indonesia's multiculturalism is not only an advantage, but also a challenge for Indonesian society. Answering these challenges, KH. A Hasyim Muzadi explained that the element of Wasathiyah Islam is a requirement to face the challenges faced by the Indonesian people.